(untitled) (Cardiovascular Journal, 2015)
Cardiac transplantation is one of the greatest medical marvels of the twentieth century. Performing this miraculous operation on 3rd December 1967, Dr. Christiaan Barnard, an unknown surgeon from the then apartheid state of South Africa suddenly became an international celebrity. Probably no single procedure in the history of medicine had attracted so much media and public attention. But there were many who thought that he didnt deserve much of this glory. A lion share of this should have gone to somebody else. Although Barnard completed the final step in the road to transplant, it was the end product of serious research work carried out in many centers around the World. Most important was Stanford University Medical Center, Palo Alto, California USA, where Dr. Norman Edward Shumway was engaged in transplantation related research work along with his junior colleague Dr. Richard Lower. The most of the techniques used in cardiac transplantation today were actually developed by Dr. Shumway and his team. Barnard worked in the same unit with Shumway at University of Minnesota when he came to USA. He visited USA again in 1966 when he observed the works of Shumways research partner Dr. Richard Lower. During both of his visits he had adopted many techniques from the research work of his American counterparts and later used in his unique accomplishment. Barnard succeeded utilizing techniques developed through Shumways painstaking work over the years depriving Shumway much of the glory he deserved. Both later on continued in the development of transplantation when most others left because of poor outcome. Shumway excelled the technical details and Barnard drew media and public attention to the importance of this procedure. After almost five decades the name of Barnard is still well known by the common people around the World; whereas Shumway remains unknown even to most of the cardiac surgeons as well. This was the destiny of the two main heroes credited behind this exciting medical accomplishment. Here lies a very interesting story, the tale of two surgeons. Cardiovasc. j. 2015; 8(1): 82-86